Global Burden of Lip and Oral Cavity Cancer From 1990 to 2021 and Projection to 2040: Findings From the 2021 Global Burden of Disease Study - Mingxing Chen; Jiangxi Li; Wei Su; Junming Huang; Chuanzhen Yang; Rui Li; Gang Chen (Cancer Medicine, 2025)
ABSTRACT Background The aim of this study was to estimate the global burden of lip and oral cavity cancer (LOC) and its trends in different genders, age groups, regions, and countries globally. Methods Data were sourced from the Global Burden of Disease 2021 study. Results During the 32‐year period, a 92.92% and 113.94% increase was estimated in the absolute counts of LOC deaths and disability‐adjusted life years (DALYs), respectively. Throughout the 32‐year period, males exhibited higher age‐standardized rates (ASRs) of incidence (ASIRs), prevalence (ASPRs), mortality (ASMRs), and DALYs (ASDRs) related to LOC. The age group of 60–64 years consistently recorded the highest numbers of new and prevalent cases across the years 1990, 2019, and 2021. In 2019 and 2021, the highest ASMR and ASDR were observed in individuals aged 95 years and older. Regions with low‐middle and low socio‐demographic index (SDI) consistently showed higher ASMRs and ASDRs associated with LOC from 1990 to 2021. Eastern Europe, South, North, and Southeast Asia exhibited a concentration of countries with higher ASIRs, ASPRs, ASMRs, and ASDRs in 2021. South Asia maintained high levels of ASIRs, ASPRs, ASMRs, and ASDRs in 2021. In 2021, Palau recorded the highest ASIR, ASPR, ASMR, and ASDR, followed by Pakistan. Projections indicate that ASIR, ASPR, ASMR, and ASDR are expected to increase by 7.40%, 10.10%, 2.85%, and 4.60%, respectively, from 2021 to 2040. Conclusion LOC remains a critical public health concern that requires immediate attention, particularly among certain demographics such as males, aged 60–64 or 95 and older, as well as in low‐ and middle‐SDI regions, particularly Eastern Europe, South Asia (notably Pakistan), North Asia, and Southeast Asia.